(untitled) (Journal of the College of Basic Education, 2023)
I do not want to introduce the personality of this author, as his nickname “Al-Jahiz” is more known than his nickname.“Abu Othman” is less famous, and his books are more famous than him. “A book may favor its owner, and he advances.”Its author” (1) by Al-Jahiz himself, and Al-Jahiz loved the book as a reader and an author.He spent his entire life as a learner, teacher and scholar, and this long continuous effort has resulted in the authoring of “many books.”She is well-known for her support of religion, for the story of the sect of opponents, for morals and morals, and forKinds of seriousness and jest, and people have circulated them and read them, and they know their virtues, and if the sane person considersGlory is something written by knowledge - it is not about impregnating minds, sharpening minds and knowing the origins of speechAnd Jawahirah, A Communication of the Controversy with Islam and the Doctrines of Retreatment - Books Similar to Them” (2), which makes the readerIn front of a brilliant author who worked diligently in collecting, and possessed “of intelligence, quickness of mind, and memorization, so thatHe was widely mentioned, exalted his worth, and dispensed with description.” (3) He followed a method of writing that set him apart from others.scholars of his time, and no one preceded him, and none of those who came after him were able to catch up with him.As a result of all this, his envy and his admirers abounded, and this affected himself as a fine writer.He was a sensitive person, until he suffered from the troubles and failures of writing.From the criticisms of his readers and their criticisms of his books, he admonished them, was kind to them and prayed for them, and he became angry with his envy.challengers against him, so he warned them and was afraid of them, and as a result of this and that he was careful in his writing and worked hardEdit his books.